Mobile 3D Mapping Using Geodetic Drones and GPS Navigation - Berun, Denys; Filipets, Maksym; Chubakova, Alina; Virchenko, Viktor (Academic journal Industrial Machine Building Civil Engineering, 2025)
The paper examines current trends in the development of geodetic mapping, with a particular focus on comparing traditional methods with innovative approaches. It is noted that classical techniques, such as the use of theodolites, levels, and GPS receivers – are still widely employed in engineering geodesy, although they present several limitations, including high labor intensity, the need for qualified personnel, and significant time consumption. At the same time, there is growing interest in automated solutions, particularly the use of unmanned aerial vehicles (UAVs), which enable rapid and accurate spatial data acquisition with minimal resource expenditure. The article emphasizes the importance of evaluating the effectiveness of different mapping methods in terms of accuracy, execution speed, and cost-efficiency, which is especially relevant in the context of the rapid development of the engineering and construction sectors.
Keywords: mapping; geodesy; mobile unmanned aerial vehicles; theodolite; level; GNSS